Pengaruh Inklusi Keuangan, Literasi Keuangan Dan Inovasi Produk Terhadap Kinerja UMKM Batik Laweyan Surakarta - Reo Anggara Putra (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Laweyan Batik Village is a village for batik craftsmen and entrepreneurs in Solo. This research was created with the aim of analyzing the significance of the influence of financial inclusion, financial literacy and product innovation on the performance of Batik Laweyan Surakarta MSMEs. This research uses qualitative and quantitative research types. The data sources used are primary data and secondary data. The population in this study was all 88 Batik Laweyan MSMEs. The sample in this study was taken as many as 88 respondents using census techniques. The data analysis techniques used in this research are descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination. The results of this research using multiple linear regression analysis show that financial inclusion has no significant effect on the performance of Batik Laweyan MSMEs, financial literacy has a significant effect on the performance of Batik Laweyan MSMEs and product innovation has a significant effect on the performance of Batik Laweyan MSMEs. The results of the F test calculation have a calculated F value of 41.589 with a p-value of 0.000 < 0.05, so Ho is rejected and Ha is accepted, meaning the model is correct. The coefficient of determination (adjusted R2) for this model is 0.583, meaning that the contribution of the independent variables (financial inclusion, financial literacy and product innovation) to the dependent variable (MSME performance) is 58.3%..